Respuesta de la interacción fungicidas y dosis de fertilizantes, a la incidencia del complejo manchado de grano en el cultivo de arroz de secano en la zona de Babahoyo - Pinto Maridueña, José Moasir (2016)
SUMMARY The work was carried out in the lands of the experimental farm of the Ability of Agricultural Sciences of the Technical University of Babahoyo, located in Km. 7,5 of the road Babahoyo-Montalvo. Ten treatments and three repetitions were investigated. The objective of this investigation was to evaluate the answer of the interaction fungicides and dose of fertilizers, to the incidence of the spotted complex of grain in the cultivation of unirrigated land rice; to determine the efficiency of the fungicidal interaction and fertilizers in the yield; to establish the effect of the treatments applied about the incidence and severity of the spotted one of grain; and to carry out the economic analysis of the treatments. He/she was carried out the siembra of rice variety INIAP-16 in parcels of 20 m2. The treatments were distributed in a design of divided parcels. For the evaluation of stockings the test was used from Tukey to 5 significancia%. At the end of the cycle of the cultivation height of plants, macollos number for m2 was evaluated, grains for panícula, longitude and number of panículas m2, days to floración, days to crop, number of grains for panícula, weight 1000 seeds, yield for hectare, incidence of the patógeno, severity of damage, causal agent's identification and economic analysis. The results determined that the application of a program of fungicides with Tebuconazol + copper Sulfate 0,5 L/ha more a fertilization balanced with 140-60-90 kg/ha of N-P-K, diminishes the incidence and damage of the spotted one of grain in the cultivation of rice, achieving a yield of 5014,3 kg/ha.